Frontier efficiency, capital structure, and portfolio risk: An empirical analysis of U.S. banks - Dong Ding; Robin C. Sickles (BRQ Business Research Quarterly, 2018)
Firm' ability to effectively allocate capital and manage risks is the essence of their production and performance. This study investigated the relationship between capital structure, portfolio risk levels and firm performance using a large sample of U.S. banks from 2001 to 2016. Stochastic frontier analysis (SFA) was used to construct a frontier to measure the firm's cost efficiency as a proxy for firm performance. We further look at their relationship by dividing the sample into different size and ownership classes, as well as the most and least efficient banks. The empirical evidence suggests that more efficient banks increase capital holdings and take on greater credit risk while reducing risk-weighted assets. Moreover, it appears that increasing the capital buffer impacts risk-taking by banks depending on their level of cost efficiency, which is a placeholder for how productive their intermediation services are performed. An additional finding, is that the direction of the relationship between risk-taking and capital buffers differs depending on what measure of risk is used."
Keywords: 650; Capital regulation; Frontier efficiency; Risk; Firm performance